An apology for M. Antonia Bourignon: in four parts ... : To which are added two letters ... containing remarks on the preface to the Snake in the grass [by C. Leslie] and Bourignianism detected [by J. Cockburn] : as also some of her own letters - Garden, George (Puritan collection of English and American literature, 1699)
1. An abstract of her sentiments and a character of her writings. -- 2. An answer to the prejudices raised against them. -- 3. The evidences she brings of her being led by the spirit of God. -- 4. An abstract of her life.